2021
DOI: 10.1002/ajmg.a.62524
|View full text |Cite
|
Sign up to set email alerts
|

Novel DIP2C gene splicing variant in an individual with focal infantile epilepsy

Abstract: Disco‐interacting protein 2 C (DIP2C) encodes a disco‐interacting protein and is highly expressed in the nervous system. Most variants of DIP2C are microdeletions on chromosome 10p15.3. This study reports a 17‐month‐old infant with focal infantile epilepsy who has a single‐nucleotide variation in DIP2C that results in alternative splicing. The de novo variation (NM_014974.3: c.1057+2T>G) in DIP2C was uncovered through whole‐exome sequencing. Minigene assays were performed and verified the alternative splicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…All the examined patients had developmental difficulties ( n = 11) or language disorder ( n = 10) (Descipio et al 2012 ). A recent study reported a case of a 17-month-old female with focal infantile epilepsy, dysmorphic features, and developmental delays in motor developmental coordination and in receptive and expressive language (Yang et al 2022 ). WES identified the de novo variant NM_014974.3 (DIP2C): c.1057 + 2T>G that was shown by minigene transfection assay to lead to DIP2C alternative splicing and an 80 bp deletion in Exon 8 (Yang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the examined patients had developmental difficulties ( n = 11) or language disorder ( n = 10) (Descipio et al 2012 ). A recent study reported a case of a 17-month-old female with focal infantile epilepsy, dysmorphic features, and developmental delays in motor developmental coordination and in receptive and expressive language (Yang et al 2022 ). WES identified the de novo variant NM_014974.3 (DIP2C): c.1057 + 2T>G that was shown by minigene transfection assay to lead to DIP2C alternative splicing and an 80 bp deletion in Exon 8 (Yang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a case of a 17-month-old female with focal infantile epilepsy, dysmorphic features, and developmental delays in motor developmental coordination and in receptive and expressive language (Yang et al 2022 ). WES identified the de novo variant NM_014974.3 (DIP2C): c.1057 + 2T>G that was shown by minigene transfection assay to lead to DIP2C alternative splicing and an 80 bp deletion in Exon 8 (Yang et al 2022 ). Furthermore, we detected two loss-of-function DIP2C variants in two ASD individuals upon mining published genetic data from 16,877 ASD individuals (Zhou et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…c.1057 + 2T > G that was shown by minigene transfection assay to lead to DIP2C alternative splicing and an 80 bp deletion in Exon 8(Yang et al, 2022). Furthermore, we detected two loss of function DIP2C variants in two ASD individuals upon mining published genetic data from 16,877 ASD individuals(Zhou et al, 2022).PARD3 is essential for cell polarity and nervous system development (X Hirose et al, 2022)…”
mentioning
confidence: 83%
“…Age at first word ranged from 10 months to 3 years, and 11 patients spoke their first word after 14 months (Figure 1). (Yang et al, 2022). Another patient had a thin corpus callosum without seizures and a third had a small/absent pituitary gland.…”
Section: Case Reportsmentioning
confidence: 99%
“…The clinical description included asthma and migraines in addition to autism, but further details were not provided. Thus, although there is some evidence that DIP2C plays a role in cognition, reports of pathogenic variants in this gene are rare (Yang et al, 2022).…”
mentioning
confidence: 99%